Preliminary analysis and exploration of big data service for agriculture,countryside and farmers - Zhongfu SUN; Jinxiang CHU; Juncheng MA; Keming DU; Feixiang ZHENG (大数据)
The issues of agriculture,countryside and farmers are receiving a lot of concerns in China.The development of big data technology brings new opportunities to solve the issues.Firstly,the role of big data to promote the development of wisdom agriculture was analyzed.Then,the basic characteristics,connotation and development trend of agricultural big data were summarized and the promotion of big data technology to solve the issues of agriculture,countryside and farmers was discussed.A sound exposition of the bottleneck and main problems of agricultural big data was presented.Finally,the path of big data technology serving agriculture,countryside and farmers,including governmental guidance and promotion,innovation of technology,was proposed.